Student guide for quickbooks 2011 for College accounting - Price, John Ellis (McGraw-Hill, 2011)
Content shows you how to use QuickBooks 2011 software with selected end-of-chapter problems and mini practice sets from College accounting, 13e. The transactions and instructions for each problem and mini-practice sets are included in the Student Guide for Quickbooks 2011.